2014
DOI: 10.5301/ijao.5000322
|View full text |Cite
|
Sign up to set email alerts
|

Endotoxin Adsorption using Polymyxin B Immobilized Fiber Cartridges in Severe Sepsis Patients following Cardiac Surgery

Abstract: Selective LPS-adsorption is a safe and possibly effective adjunctive treatment method for severe sepsis patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Overall, this review concluded that selective LPS-adsorption was associated with improvements in clinical outcomes (significant increases in mean arterial blood pressure, + 19 mmHg; reductions in vasoactive dopamine/dobutamine dose, − 1.8 μg/kg/min; and increases in gas exchange, mean arterial partial pressure of oxygen/fraction of inspired oxygen ratio, + 32 units) and in mortality risk (risk ratio, 0.53; 95% CI, 0.43–0.65). More recently, improvements in hemodynamic indices and survival rates have also been shown following Toraymyxin hemoperfusion of patients with severe sepsis or septic shock in the randomized controlled EUPHAS trial vs conventional therapy [ 15 ], the EUPHAS 2 registry [ 16 ], and in a prospective study [ 17 ]. However, no improvement was seen in either mortality or organ failure with Toraymyxin in a study enrolling 243 patients from 18 French intensive care units [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this review concluded that selective LPS-adsorption was associated with improvements in clinical outcomes (significant increases in mean arterial blood pressure, + 19 mmHg; reductions in vasoactive dopamine/dobutamine dose, − 1.8 μg/kg/min; and increases in gas exchange, mean arterial partial pressure of oxygen/fraction of inspired oxygen ratio, + 32 units) and in mortality risk (risk ratio, 0.53; 95% CI, 0.43–0.65). More recently, improvements in hemodynamic indices and survival rates have also been shown following Toraymyxin hemoperfusion of patients with severe sepsis or septic shock in the randomized controlled EUPHAS trial vs conventional therapy [ 15 ], the EUPHAS 2 registry [ 16 ], and in a prospective study [ 17 ]. However, no improvement was seen in either mortality or organ failure with Toraymyxin in a study enrolling 243 patients from 18 French intensive care units [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the application of extracorporeal approaches targeting pathogens, pathogen-associated molecular patterns, or endogenous mediators of inflammation in the circulation, their combination with appropriate diagnostic tools is therefore highly warranted. The application of PMX-DHP together with an endotoxin activity assay (80) is a first step in this respect, and other extracorporeal approaches targeting pathogens or inflammatory mediators in the circulation should be based on similar considerations, applying point-of-care diagnostic systems with minimal sample handling and short time-to-result to move toward personalised, biomarker-guided, adjunctive sepsis treatments.…”
Section: Patient Heterogeneity In Sepsis and The Need For A Theragnosmentioning
confidence: 99%
“…Bakulev NSPCCS in 2009-2016, showed the safety and efficacy of the combined therapies mentioned above. [53,54] We observed that the combination of LPS-adsorption and HDF filters with high cut-off EMiC2 membranes led to a 34% MAP increase [from 76 (65)(66)(67)(68)(69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81) to 90 (85-102) mmHg, P < 0.001] with reduced vasopressor and inotropic support. The increase in MAP during LPS-adsorption with CPFA was 12% with the significant decrease in vasopressor support [the dose of noradrenaline was halved from 0.2 (0.15-0.3) to 0.1 (0.05-0.15) µg/kg/min, P = 0.024].…”
Section: Extracorporeal Blood Purification In Complex Intensive Theramentioning
confidence: 99%
“…[64][65][66][67] LPS-adsorption using Toraymyxin-PMX-20R Polymyxin B immobilized fiber cartridges was found to be effective, simultaneously acting through sorption and apheresis on bacterial endotoxin, systemic inflammatory mediators and activated immune cells. [59][60][61]68,69] CPFA performs an immunomodulatory role by acting on inflammatory mediators (interleukin-1β, -6, -8, -10, -18, tumor necrosis factor-α and others) via various mass transfer mechanisms such as diffusion, convection and adsorption. The advantages of CPFA include the passage of plasma (and not blood) through the sorption column, which increases the contact time with the sorption surface and improves the efficiency of the procedure.…”
Section: Extracorporeal Blood Purification In Complex Intensive Theramentioning
confidence: 99%